2021
DOI: 10.1098/rspa.2020.0778
|View full text |Cite
|
Sign up to set email alerts
|

The avian compass can be sensitive even without sustained electron spin coherence

Abstract: Theoretical studies indicating the presence of long-lived coherence in the radical pair system have engendered questions about its utilitarian role in the avian compass. In this paper, we investigate the role of electron spin coherence in a multinuclear radical pair system including its impact on compass sensitivity. We find that sustenance of long-lived electron spin coherence is unlikely in a multinuclear hyperfine environment. After probing the role of the hyperfine interactions in the compass, we affirm th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 42 publications
(97 reference statements)
1
18
1
Order By: Relevance
“…Surprisingly, an anti-correlation with respect to µ[ Ci ] is observed that is present in both the UD and ST basis, but larger in the former. Specifically, ∆ S is found to anti-correlate with µ[ CE,UD r ], which is based on the same coherence measure as used by Jain et al 32 , giving rise to a remarkable correlation coefficient of R = −0.927. In contrast, a positive (but weaker) correlation is observed with respect to the ∆[ CE,ST r ] measure.…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…Surprisingly, an anti-correlation with respect to µ[ Ci ] is observed that is present in both the UD and ST basis, but larger in the former. Specifically, ∆ S is found to anti-correlate with µ[ CE,UD r ], which is based on the same coherence measure as used by Jain et al 32 , giving rise to a remarkable correlation coefficient of R = −0.927. In contrast, a positive (but weaker) correlation is observed with respect to the ∆[ CE,ST r ] measure.…”
Section: Resultsmentioning
confidence: 94%
“…Large spin system electronic coherence. Previous studies on coherence in the avian compass typically use systems with a modest number of nuclear spins (only one or 5-6) and often randomly assumed hyperfine interactions 28,29,32,38,41 . Under the assumptions as laid out above, we have been able to overcome this limitation and evaluate fidelities and coherence measures for flavintryptophan and flavin-tyrosine radical pairs with up to 21 nuclear spins and judiciously chosen hyperfine parameters, as summarized in the Supplementary Information (SI).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations